Spin dynamics in cuprate perovskites - Sherman, A.; Schreiber, M. (Физика низких температур, 2006)
Results obtained with the use of the t–J model of Cu–O planes and Mori’s projection operator
formalism are compared with data of neutron scattering experiments in lanthanum and yttrium
cuprates. This comparison allows us to interpret the intensive peak at the antiferromagnetic wave
vector observed in yttrium cuprates as a manifestation of excitations of localized Cu spins. The
high-frequency incommensurability detected both in lanthanum and yttrium cuprates is connected
with the dispersion of these excitations, while the low-frequency incommensurability arises due to
a dip in the spin-excitation damping at the antiferromagnetic wave vector. For moderate doping
the dip stems from the weakness of the interaction between the spin excitations and holes near hot
spots. It is conjectured that the dissimilarity of the susceptibility frequency dependencies in yttrium
and lanthanum cuprates may be connected with different values of the hole bandwidth and
damping in these crystals.